Genetic Analysis for Wood Parameters in Full-Sib Seedling Progeny Clones of Populus deltoides - Kandpal, Vidisha; Pande, P. K.; Dhiman, R. C. (Indian Forester, 2019)
The present study deals with the intra-ramet radial, inter-individual and inter-progeny variations in wood anatomical traits and specific gravity of Populus deltoides clones raised from twelve full-sib progenies collected from Gadariyabag, Kichha (Udham Singh Nagar, Uttarakhand) India. The genetic analysis of wood traits viz., fibre dimensions, vessel element dimensions and specific gravity was also performed. Full-sib progenies showed significant variations for all the parameters studied. Intra-ramet radial variations and inter-individual variations were significant for all the parameters studied. Broad sense heritability (H2) for wood traits ranged from 0.41 (vessel element diameter) to 0.90 (fibre wall thickness). Other wood traits namely fibre length, fibre diameter, lumen diameter and vessel element length showed the heritability values as 0.59, 0.65, 0.53 and 0.69 respectively. Specific gravity showed the broad sense heritability 0.21. Positive genetic gain and genetic advance showed the possibility of improvement of species for wood traits. All the individuals of full-sib progenies were clustered into five clusters at 6 rescaled distance cluster combine. Individual number 51 of (WSL-A/49 Â± WSL-A/26) showed higher values for most of the wocd traits. Moreover, 11 individuals clustered into cluster 3 showed better wood traits, may well be used in tree improvement programs of the species.